2019
DOI: 10.3389/fpsyg.2019.01185
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Hierarchical Influences of the Big-Five Dimensions and Anxiety Sensitivity on Anxiety Symptoms in Children

Abstract: Anxiety sensitivity (AS), namely the fear of anxiety symptoms, has been described as a precursor of sub-threshold anxiety levels. Sexton et al. (2003) posited that increased AS would arise from an elevated neuroticism and that both would act as vulnerability factors for panic disorder (PD), obsessive-compulsive disorder (OCD), and generalized anxiety disorder (GAD) symptoms. Accordingly, this study aimed to (1) evaluate the applicability of this model to a pediatric population and (2) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 127 publications
(185 reference statements)
0
4
0
Order By: Relevance
“…Recent work suggests that is likely personality and health outcomes is linked through 'assimilative' processes, with personality factors tending to predict behavioral response pattens and the likelihood of influence by situational facilitators/barriers (McCrae and Sutin, 2018). For example, individuals who are more neurotic and less open to experience exhibit higher levels of anxiety sensitivity (Wauthia et al, 2019) and experiential avoidance (Mohammadkhani et al, 2016), which may lead them to engage in avoidant behavioral patterns (Sirois, 2015;.…”
Section: Personality and Self-regulatory Behavior Change Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work suggests that is likely personality and health outcomes is linked through 'assimilative' processes, with personality factors tending to predict behavioral response pattens and the likelihood of influence by situational facilitators/barriers (McCrae and Sutin, 2018). For example, individuals who are more neurotic and less open to experience exhibit higher levels of anxiety sensitivity (Wauthia et al, 2019) and experiential avoidance (Mohammadkhani et al, 2016), which may lead them to engage in avoidant behavioral patterns (Sirois, 2015;.…”
Section: Personality and Self-regulatory Behavior Change Techniquesmentioning
confidence: 99%
“…Similarly, several canonical personality factors have a high degree of heritability, including trait levels of neuroticism and openness (Jang et al, 1996). Although the degree of heritability for personality traits is somewhat lower than that observed for executive functioning, this may partly obscure the degree to which core temperamental elements of personality development, such as anxiety sensitivity, may play (Wauthia et al, 2019). In both cases, evidence increasingly suggests a vulnerability model of genetic transmission, in which predisposing vulnerabilities in cognitive and psychological phenotypic markers confer risk of developing an array of subsequent clinical disorders and with adaptive functioning more broadly (Bagby et al, 2008;Mertens et al, 2022).…”
Section: Intermediate Phenotypes Of Cognitive and Psychological Functionmentioning
confidence: 99%
“…Personality traits seem to have a role in the development of anxiety disorders. Recent studies have found that a high level of Neuroticism predicts social phobia, panic disorder and generalized anxiety disorder [82]. Higher Neuroticism and lower Conscientiousness levels are related to an increase in anxiety and lower Extraversion is associated with social phobia [52].…”
Section: Medical Perspective On Personality Traitsmentioning
confidence: 99%
“…It was also observed that AS, even after controlling the effect of NA, is a significant predictor of developing one of the anxiety disorders (Schmidt, Mitchell, & Richey, 2008 ). Further, the evidence also supported the role of AS in the development of emotional disorders in children (Brown, Meiser-Stedman, Woods, & Lester, 2016 ; Hernandez Rodriguez, 2015 ; Ho, Dai, Mak, & Liu, 2018 ; Knapp, Blumenthal, Mischel, Badour, & Leen-Feldner, 2016 ; Raines et al ., 2020 ; Viana et al ., 2018 ; Wauthia et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%